CHRONIC RECURRENT APHTHOUS STOMATITIS IN GASTROINTESTINAL DISEASES: ORAL MICROFLORA AND IMMUNOLOGICAL STATUS - Kamilov Kh. P.; Ergashev N. A.; Takhirova K. A.; Kadirbaeva A. A.; Komilov E. J.; Kuchkarova L. S.; Bakhramova F. N. (Modern American Journals, 2025)
The conducted study is devoted to the study of the pathogenesis of recurrent aphthous stomatitis. The question of the etiopathogenesis of this disease still remains open. However, the prevalence of the disease is growing with all modern research methods. There were 50 patients examined in 2021 – 2023 years. All the patients were examined at the Hospital Therapeutic Dentistry Department of Tashkent State Dental Institute and diagnosed with resurrent aphthous stomatitis.10 patients without oral pathology were examined as control.The microflora in biomaterials was determined in the bacteriological laboratory of the second clinic of the Tashkent Medical Academy. The immunological analysis parameters of blood were determined in the laboratory of "IMMUNOGEN TEST" LLC. Determination of the cellular component of the immune system was carried out using venous blood taken from patients. The main subpopulation of lymphocytes in peripheral blood was studied.Obtained results showed natural imbalance in the microbiocenosis of the oral cavity. It has been shown that the origin of recurrent aphthous stomatitis may be the result of damage to the oral epithelium caused by a T-cell immune response.
Keywords: Recurrent aphthous stomatitis, clinical course, microbiology, immunology.